The general overview and marketing strategy in xyz real estate agent after the organization restructuring - Thalib, Karimah; Aprianingsih, Atik (Journal of Business and Management, 2019)
Abstract- This study examines the general overview of XYZ Real Estate Agent, as well as external conditions that could affect real estate market, in order to develop a marketing strategy to overcome the decrease of sales due to declining number of marketing agent problem. This organization formerly known as Century21 for 7 years before the owner decided to stop the franchise and built his own business, XYZ Real Estate Agent on 2015. As a service based business, a real estate agency heavily relied on its marketing strategy and its marketing agents. However, XYZ Real Estate Agent has been facing an issue regarding a significant decrease of sales performance. The primary data were obtained through observations and interviews. While the secondary data were collected through books, journals, and articles on the internet. This study used SWOT and TOWS methodology by conducting internal and external analysis beforehand.It was discovered that the XYZ Real Estate Agent could implement several strategies by maximizing its strengths and minimizing its weaknesses through utilization of digital marketing, actively looking for information as AREBI member, collaborate with competitor’s marketing staff. In addition, it is important for a marketing staff to build and maintain social networks and trust.Keywords: Bandung Property, Marketing Strategy, Real Estate Agent, Restructuring